Development of a web-based futsal learning model methodology - Amansyah Amansyah; Raswin Raswin; Muhammad Ishak; Argubi Silwan; Boby Helmi; Benny Aprial; Afri Tantri (LPMPP Universitas Negeri Yogyakarta, 2026)
Based on background and research objectives, this study is expected that students in learning independently will be more efficient, helping students' knowledge, competence, and academic achievement in futsal courses. The purpose of this research is to produce a learning model for basic futsal technical skills based on world wide web (www), with product results packaged in the form of applications that can be used both in learning activities and in independent practice to facilitate the delivery of Futsal course learning material. This study uses research and approaches adopted from Borg and Gall which are grouped into three stages, 1) identification stage, 2) development stage, and 3) evaluation stage. The results of the effectiveness test above where the world wide web learning model in the futsal course was tested on 30 students of the faculty of sports science and the results obtained were eleven people were effective on student thinking skills, nine people were quite effective, six people were less effective and two people were not effective on the use of the word wide web learning model. The conclusion of the research results through the web-based Futsal learning model can increase students' knowledge and skills in playing Futsal effectively and efficiently collaboration.